Developing Social Studies Teachers’ Professionalism in Addressing Learning Challenges - Depi Fibriyanti; Rifa’i Rifa’i (CV. Generasi Insan Rafflesia, 2026)
Teacher professionalism is an important factor in determining the success of the learning process, including in Social Studies (IPS). In its implementation, IPS learning still faces various problems, such as low student interest in learning, the use of monotonous learning methods, limited learning media, and low utilization of technology in the learning process. This study aims to analyze the development of IPS teacher professionalism in addressing learning problems in schools. The research method used is a qualitative approach with a literature study type. Data were obtained from various sources such as books, scientific journals, articles, and previous research results relevant to teacher professionalism and IPS learning. The results show that the development of IPS teacher professionalism can be done through improving pedagogical competence, professional competence, social competence, and personality competence. In addition, IPS teachers also need to improve their ability to utilize digital technology, develop innovative learning media, and implement creative and interactive learning strategies. The development of teacher professionalism has been proven to help overcome various problems in IPS learning so that the learning process becomes more effective, interesting, and student-centered. However, several obstacles still exist such as lack of training, limited facilities, and low support for teacher competency development. Therefore, cooperation between schools, the government, and teachers is needed to support the continuous improvement of the professionalism of social studies teachers.